Madagascar : A Competitiveness and Exchange Rate Assessment - Eyraud, Luc (IMF Working Papers; Working Paper ;, 2009)
The purpose of this paper is to assess Madagascar's competitiveness in recent years, using both price and nonprice indicators and an exchange rate assessment of the currency. We estimate the distance between the equilibrium and the actual real exchange rates using three methods: the macroeconomic balance approach, the external sustainability approach, and the reduced-form equilibrium real exchange rate approach. These methods suggest that in the medium term the real exchange rate is only slightly overvalued. We also carry out a comparative analysis of nonprice indicators and find that Madagascar performs less favorably than its competitors on structural competitiveness.